Systems Biomedicine Concepts and Perspectives - Liu, Edison T;Ed. Lauffenburger, Douglas A;Ed (Elsevier, 2010)
Systems biology is a critical field that seeks to define the interactions of all biological components by examining underlying biochemical and genetic processes. This title focuses on the applications of systems approaches to medical problems. It reflects the important characteristics of systems strategies in experimental biology and medicine.